Efektivitas Program Pembinaan dan Pengawasan Laporan Kegiatan Penanaman Modal oleh DPMTPSP Kota Surabaya dalam Meningkatkan Kepatuhan Pelaporan LKPM Para Pelaku Usaha di Kota Surabaya - Syaputra, Fajar Tridian (VISA: Journal of Vision and Ideas, 2024)
Investment or capital investment plays a crucial role in the government's efforts to improve the Indonesian economy. Every investor has an obligation to prepare the Investment Activity Report (LKPM). The purpose of this study is to determine the effectiveness of the training and supervision program for investment activity reports in improving compliance with LKPM reporting by businesses in Surabaya City. The method used in this research is descriptive with a qualitative approach. The required data consists of primary data. Data were obtained through observation, interviews, and documentation, while sample selection techniques used purposive sampling. Effectiveness in this study is based on 5 parameters: program understanding, target accuracy, timeliness, goal achievement, and tangible changes. The research results show that all indicators are considered effective.